RANCANG BANGUN SISTEM KONVERSI UANG LOGAM MENJADI E-MONEY BERBASIS MIKROKONTROLER DAN APLIKASI ANDROID - D M Baskara Puruhita Wija; I G A P Raka Agung; Pratolo Rahardjo (Jurnal SPEKTRUM, 2021)
Money is a medium that is used as a means of buying/selling. Indonesia uses theRupiah currency with 2 types of money used, one of which is coins. Coins are generally used intransactions of small amounts, but in some cases, coins are used in transactions of largeamounts. This caused problems in counting and sorting coins in terms of time and energy.Through this problem, a coin sorting and the counter system was developed that could beconverted into E-Money and integrated with an Android-based smartphone. The system isdesigned with 2 parts, namely hardware and software. The sorting system is created using thedifferent diameters of each coin. The counting system uses IR Sensor to detect coins andcounts on the ESP32. Testing on the system is carried out in 3 stages, namely testing the toolsystem, testing the Android application system, and testing the whole system. The system forconverting coins to e-money is made using the ESP32 as the main microcontroller withBluetooth as a medium of communication with smartphones. The coin sorting board is madeinto 4 strips and has holes the same size as the diameter of the coins. In the coin countingsystem, the tool has been able to count up to 250 coins in 8 minutes 21 seconds with anaccuracy percentage above 80%.